Factors Influencing Customers' Purchase Decision on Tiktok Video Content - Putri, Amelia Maharani; Kamilatunnisa, Nadya; Larasati, Anisa (Journal of International Conference Proceedings, 2024)
In recent years, social media is not only used as a platform for information exchange but also plays a significant role in transforming consumer shopping behavior. This research aims to analyze the factors influencing purchasing decisions in TikTok video content. The factors analyzed include the Bandwagon Effect, Visualization, User Experience (UX), Interactivity, and Search Engine Optimization (SEO). A quantitative approach was adopted, collecting data through questionnaires distributed to 100 respondents. Hypotheses were tested using regression analysis supported by SPSS software. The results revealed that each independent variable individually has a significant impact on purchasing decisions. Moreover, multiple regression analysis demonstrated that all five variables collectively influence purchasing decisions in TikTok video content. These findings are expected to help companies and businesses develop more effective social media content strategies, particularly on TikTok, to enhance promotion and increase sales.